Studi Deskriptif Kualitas Hidup Pasien Epilepsi pada Anak Usia Sekolah dan Remaja - Rahayu, Diana; Sulianingsih, F Sri; Prawesti, Ayu (Universitas 'Aisyiyah Bandung, 2018)
DESCRIPTIVE STUDY ABOUT QUALITY OF LIFE IN SCHOOL AGE AND ADOLESCENT WITH EPILEPSY ABSTRACT Epilepsy is Chronic Neurological disease which have impact in various aspects of life, such as disruption of growth, cognitive function, psychosocial aspects, inhibit of daily activities, and the risk of death which can affect quality of life patients. Consider that the risk of anxiety and depression most occured in patients which have low quality of life. The aim of this study to describe about quality of life in children and adolescent with epilepsy at one of Lv.II hospital in Cimahi. Design of this study used quantitative descriptive with sampling technique used non problability consecutive sampling. Total of sample is 40 respondent aged 8-18 years old which devided by school age (n=4) and adolescent (n=36).The instrument of this study used QOLIE-AD-48 to identify 8 dimensions related to the quality of life in people with epilepsy (PWE), with analyzing technique descriptive data statistic. The result show that mean of Total Summary score is 65,38. Dimension which have high score is School Behavior, Epilepsy Impact, dan Physical Functioning. While dimension which have lower score is Attitudes toward epilepsy, Health perception, and Stigma. According to this research, it’s so important to educate and counsel the patient related to eplilepsy disease information and the step minimalize the negative impact from society’s stigma to increase PWE’s quality of life. Key Words : Adolescent, child in school age, epilepsy, quality of life